Switchbacks near Boundaries of Small-scale Magnetic Flux Ropes in the Young Solar Wind from Parker Solar Probe Observations - Kyung-Eun Choi; Oleksiy V. Agapitov; Dae-Young Lee; Forrest Mozer; Jia Huang; Lucas Colomban; Jaye L. Verniero; Nour Raouafi (The Astrophysical Journal)
The Parker Solar Probe (PSP) mission has revealed frequent occurrences of switchbacks (SBs) and small-scale magnetic flux ropes (SMFRs) as prominent structures within the solar wind. These mesoscale features are observed across all heliocentric distances, with heightened activity in the young solar wind, such as successive SMFRs, blobs, and SBs using PSP in situ observations. One study, in particular, focuses on SMFRs observed during the intervals of PSP corotating with the Sun, which suggests a similar source of the observed solar wind. In this paper, we identified SBs at the boundaries of SMFRs as a regularly observed phenomenon and found instances where SBs and SMFRs co-occur, with the significance level α  < 0.05. The SMFR-related SBs—observed at the leading and trailing edges of an SMFR—exhibit well-organized axial co-orientations, with their polarity flipping, meaning the radial direction remains constrained while the transversal field reverses. Furthermore, the axial field directions of SMFR-related SBs appear to be more closely connected than to another SB that is spatially closer and are linked to the SMFR orientation. Our analysis of their relative geometry, which examines the alignment between SBs and the SMFR axis, reveals a distinct tendency emphasizing their correlation, further supporting the idea that the axes of SMFR-related SBs are presumably determined by the SMFR orientation. Observations suggest that a fraction of SBs are spatially and temporally associated with SMFRs, implying that processes related to SMFR boundaries may contribute to SB formation or that SBs tend to develop in magnetic environments shaped by SMFRs.